2018
DOI: 10.4103/jispcd.jispcd_408_17
|View full text |Cite
|
Sign up to set email alerts
|

The expression and functional significance of vascular endothelial-cadherin, CD44, and vimentin in oral squamous cell carcinoma

Abstract: Objectives:Ninety percent of head and neck cancers are squamous cell carcinoma which develops in the oral cavity. Metastasis is the main causative factor for death in 90% of all cancer-related deaths and begins with the invasion of tumor cells through the walls of small blood vessels or lymph vessels. A growing body of evidence has shown that vasculogenic mimicry (VM) facilitates tumor growth and cancer metastasis. The current study aimed to present the role of vascular endothelial (VE)-cadherin, CD44, and vim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
5
27
0
2
Order By: Relevance
“…Cancer led to approximately 9.6 million deaths worldwide in 2018 and is the second leading cause of death. 33 CD44 is highly expressed in cancer cells and cancer-associated ECs, 3,[34][35][36] and its expression has been observed to be associated with poor prognosis for many cancer types, including colorectal carcinoma, infiltrating ductal carcinoma, gastric adenocarcinoma, bladder cancer, head and neck cancer. [37][38][39][40][41][42][43] Although CD44 is widely recognized as a cancer stem marker 3,44 and promotes cancer progression and metastasis by regulating cancer cell stemness, 3,44,45 survival, [46][47][48] proliferation, [47][48][49] and adhesive and invasive properties, [50][51][52][53] the protumorigenic effects of CD44, at least partially, rely on its tumor angiogenesis-promoting activities.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer led to approximately 9.6 million deaths worldwide in 2018 and is the second leading cause of death. 33 CD44 is highly expressed in cancer cells and cancer-associated ECs, 3,[34][35][36] and its expression has been observed to be associated with poor prognosis for many cancer types, including colorectal carcinoma, infiltrating ductal carcinoma, gastric adenocarcinoma, bladder cancer, head and neck cancer. [37][38][39][40][41][42][43] Although CD44 is widely recognized as a cancer stem marker 3,44 and promotes cancer progression and metastasis by regulating cancer cell stemness, 3,44,45 survival, [46][47][48] proliferation, [47][48][49] and adhesive and invasive properties, [50][51][52][53] the protumorigenic effects of CD44, at least partially, rely on its tumor angiogenesis-promoting activities.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%
“…25 A number of studies have revealed a positive relationship between CD44 expression and microvessel density (MVD), which is a characteristic of angiogenesis, in human tumor samples. 35,36,38,[54][55][56][57][58][59][60] A parallel increase in CD44 expression and high MVD has been observed in a variety of cancer types, such as infiltrating ductal carcinoma, 38 renal cell carcinoma, 56 and oral squamous cell carcinoma 35 (summarized in Table 1). In the oral orthotopic carcinogenesis mouse model, CD44 expression becomes upregulated in perivascular area along with excessive blood vessel formation during cancer progression.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%
“…Therefore, it is urgent to understand the molecular mechanisms of OSCC tumorigenesis and metastasis. Several molecular signaling and pathways contribute to the development and metastasis of OSCC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor growth and metastasis are correlated to the function and the altered expression level of many proteins, as well as gene mutations (5,8,(22)(23)(24). In addition, cancer cell invasion and metastasis are correlated to the level of cancer cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation